COST ANALYSIS OF TRANSPERINEAL PROSTATE BIOPSY WITH VY DEVICE AND TRANSRECTAL PROSTATE BIOPSY AT HASAN SADIKIN ACADEMIC MEDICAL CENTER BANDUNG: A RETROSPECTIVE STUDY - Pramod, Sawkar Vijay; Muhamad, Prasojo (Indonesian Journal of Urology, 2026)
Objective: This study aimed to determine the analysis for the cost of Transperineal Prostate Biopsy using the VY device (VY-TPPB) and Transrectal Prostate Biopsy (TRPB). Material & Methods: This study is a retrospective descriptive study with the sample being patients who underwent TRPB or TPPB at Hasan Sadikin Academic Medical Center, Bandung for the period of January 2019 to December 2023. The total sample was 108 patients, with 53 patients having undergone TPPB and 55 patients having undergone TRPB. The cost for each procedure are then analyzed and divided into pre-procedure, intra-procedure, and post-procedure costs. Results: The average cost per patient is Rp 8.005.356 (USD 507.4) for VY-TPPB procedures and Rp 11.748.976 (USD 744.7) for TRPB procedures. Comparison of the average costs of VY-TPPB with TRPB was higher in the TRPB group (p < 0.05). Comparison of the average intra-procedure and post-procedure costs was also significantly higher in the TRPB group (p < 0.05). There was no significant difference in pre-procedure costs. Conclusion: The TPPB-VY technique is more cost-effective compared to TRPB, although further research is needed to understand the advantages of each method. Keywords: Prostate biopsy, VY device, cost.